MENINGKATKAN KETERAMPILAN MEMBACA NYARING MELALUI MODEL PEMBELAJARAN COOPERATIVE SCRIPT DI SEKOLAH DASAR - Wulandari, Novia; Lyesmaya, Dyah; Nurasiah, Iis (Program Studi PGMI, 2019)
This study aims to describe the application of Cooperative Script learning models to improve loud reading skills. The research method used was Classroom Action Research (CAR). This research design used the Kemmis and Mc Taggart models conducted in two cycles. Each cycle consists of planning, implementing actions, observing, and reflecting. Participants in this study were 3rd grade students of SDN Lembursitu with 24 students, consisting of 14 male students and 10 female students. Data collection techniques were test, observation, and documentation. The results of research on teacher activity in the first cycle showed 69 point with a good category while student activities showed 68 point with an active category. The increase in cycle II teacher activity reaches 82 point with a very good category and student activity reaches 84 point with a very active category. Before the cycle, only 29% student achive the minimum score achievement. The score in the first cycle increased to 58%. At the end,the score of the second cycle acieve 87% improvement. Based on the cycles results, students loud reading skills are improved by using the CS model.